PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN THINK TALK WRITE DISERTAI MODUL HASIL PENELITIAN TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGRI 2 SUKOHARJO TAHUN PELAJARAN 2011/2012 - Prasasti, Yuniar; Muzayyinah, Muzayyinah; Maridi, Maridi (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? This research aims to find out the effectof the implementation of learning strategy Think Talk Write with module research resultstowards students? learning achievement of the class X at SMA Negeri 2 Sukoharjo. This study is aquasi-experimental studies which use Posstest Only Control Group Design. The independent variable in this research is the application of learning srategy, the Think Talk Write with module research results where as the dependent variable is students? achievement in learning biology at 3 levels?. Namely, cognitive, affective and psychomotor. The population of the study is the entire of class X at SMA Negeri 2 Sukoharjo in academic year 2011/2012.The samplesis taken upon control group and treatment group. The sample is taken by using Cluster Random Sampling method. The data are collected byusingtest (for cognitive achievement) where as for the affective and psychomotor aspects the data are taken by using observation methods. The obtained data that is analyzed by using t-test. The result shows the implementation of learning strategy Think Talk Write with module research resultshas taken good effect towards students? achievement in affective and psychomotor aspects, but has not on the cognitive achievement students in class X of SMA Negeri 2 Sukoharjo. Keywords: LearningStrategy, Think Talk Write, Learning Achievement